Negative Factors Affecting Interest in Learning: From a Teacher's Perspective - Arif, Muhammad Dallun; Alazrah, Meza; Musdalifah, Nurul (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research examines the perspective of class teachers at SDN 105 Sidorukun regarding negative factors that influence students' interest in learning. So, this type of research is qualitative descriptive research. The subjects of this research were class teachers at SDN 105 who taught or were assigned to the counseling guidance process. The data collection technique uses interview techniques, so the results of the interviews are described by ordering the largest to smallest negative factors that influence students' interest in learning. According to the class teacher's perspective, this study found that the most dominant negative factor influencing interest in learning was playing more actively than studying.